LncRNA2Function: a comprehensive resource for functional investigation of human lncRNAs based on RNA-seq data. (December 2015) - Jiang, Qinghua; Ma, Rui; Wang, Jixuan; Wu, Xiaoliang; Jin, Shuilin; Peng, Jiajie; Tan, Renjie; Zhang, Tianjiao; Li, Yu; Wang, Yadong
Abstract Background The GENCODE project has collected over 10, 000 human long non-coding RNA (lncRNA) genes. However, the vast majority of them remain to be functionally characterized. Computational investigation of potential functions of human lncRNA genes is helpful to guide further experimental studies on lncRNAs. Results In this study, based on expression correlation between lncRNAs and protein-coding genes across 19 human normal tissues, we used the hypergeometric test to functionally annotate a single lncRNA or a set of lncRNAs with significantly enriched functional terms among the protein-coding genes that are significantly co-expressed with the lncRNA(s). The functional terms include all nodes in the Gene Ontology (GO) and 4, 380 human biological pathways collected from 12 pathway databases. We successfully mapped 9, 625 human lncRNA genes to GO terms and biological pathways, and then developed the first ontology-driven user-friendly web interface namedlncRNA2Function, which enables researchers to browse the lncRNAs associated with a specific functional term, the functional terms associated with a specific lncRNA, or to assign functional terms to a set of human lncRNA genes, such as a cluster of co-expressed lncRNAs. ThelncRNA2Function is freely available athttp://mlg.hit.edu.cn/lncrna2function . Conclusions The LncRNA2Function is an important resource for further investigating the functions of a single human lncRNA, or functionally annotating a set of human lncRNAs of interest.